A Prospective Cohort Study of Influences on Externalizing Behaviors Across Childhood: Results From a Nurse Home Visiting Randomized Controlled Trial - Enoch, Mary-Anne; Kitzman, Harriet; Smith, Joyce A.; Anson, Elizabeth; Hodgkinson, Colin A.; Goldman, David; Olds, David L. (Journal of the American Academy of Child and Adolescent Psychiatry, 2016)
This study investigated genetic and environmental influences on behavior in a cohort of 600 children followed prenatally to 18 years. A randomized controlled trial of prenatal/infancy nurse home visits (NHV) was conducted in 600 predominantly African American mothers and their firstborn children from Memphis, TN. Mothers were assessed in pregnancy for mental health (MH), self-efficacy, and mastery. Mothers reported longitudinally on smoking and alcohol/drug use. The functional polymorphisms SLC6A4 5-HTTLPR, FKBP5 rs1360780 and DRD2/ANKK1 rs1800497 were genotyped together with 186 ancestry informative markers. Composite externalizing disorders (ED) continuous total scores from the mother-report Achenbach Child Behavior Checklist were included as dependent variables in regression analyses for time points 2, 6, 12, and 18 years. Behaviors at younger ages strongly predicted later behaviors (p < .0001). Children whose mothers had high self-efficacy and had received NHV were better behaved at age 2 years. Poorer maternal MH adversely influenced ED up to 12 years, but at age 18 years, maternal mastery exerted a strong, positive effect (p = .0001). Maternal smoking was associated with worse ED at 6 and 18 years. Main and interactive effects of genetic polymorphisms varied across childhood: FKBP5 rs1360780 up to age 6, 5-HTTLPR from 6 to 12, and DRD2/ANKK1 rs1800497 from 2 to 18 years. Our study suggests that maternal MH and resilience measured in pregnancy have long-lasting effects on child behavior. Maternal smoking across childhood and genetic factors also play a role. NHV had a positive effect on early behavior. Our findings have implications for prevention of pathological behaviors in adulthood. Clinical trial registration information—Age-17 Follow-Up of Home Visiting Intervention; http://clinicaltrials.gov/; NCT00708695.